Fetal lymphangioma:report of cases in Bogota, Colombia Introduction (2012)
lymphangiomas are malformations of the lymphatic system that can appear as multilobulated cavities in the neck (75%) and axilla (20%) with very few cases of extensive lymphangioma reported in the literature. The incidence of cases diagnosed prenatally is really low but causing very high mortality rate because of its relationship with complications or compression effects which can result in difficulty breathing, difficulty swallowing, fever, sudden or coinfection of the lesion. Two cases are reviewed in order to conduct a review of the literature on prenatal diagnosis and prognosis. Methodology: we present two cases with different outcome, performing an exhaustive search through PubMed MEDLINE, MD Consult, Ovid, Hinari for the last three years with MeSH terms: lymphangioma, lymphangioma, cystic, abdominal cystic lymphangioma, prenatal diagnosis, ultrasonography, prenatal. We obtained a total of 449 articles of which 18 were relevant and appropriate to include in the review, none of which was obtained in the Latin American environment. Conclusion: lymphangioma is an uncommon condition whose early diagnosis and adequate prenatal counseling helps to manage and improve newborn neonatal prognosis (MÉD.UIS.2012;25(2):149-54).